EXTERNAL ECONOMIC POTENTIAL OF OIL-PROCESSING INDUSTRY OF RUSSIA - A. Solomonov (Вестник университета)
Steady bases of development of foreign economic relations of oil refinery in our country were so far created. At the same time, a number of restrictions of realization of the external economic capacity of branch still takes place. In the article major factors and tendencies of development of foreign trade in oil products in Russia at the present stage are generalized